Antibacterial ultra-thin fiberboard and preparation method thereof
By using the NP-S produced by the reaction of phosphoryloxazolidinone and sodium sulfamate in ultrathin fiberboard, combined with the urea-formaldehyde resin adhesive and the modified porphyrin-type cobalt antibacterial agent N-Co, the problem of antibacterial treatment in the prior art affecting the strength of the glue and secondary contamination in the prior art is solved, and the effect of taking into account both the efficient antibacterial and mechanical properties is achieved.
Patent Information
- Application Number
- CN202310850605.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-07-12
AI Technical Summary
When the existing ultra-thin fiberboard is treated with antibacterial treatment, antibacterial agents have a great impact on the adhesive strength of the board and have secondary pollution, making it difficult to take into account both antibacterial and mechanical properties.
The reaction product NP-S was used to react phosphooxazolidinone with a molar ratio of 1: (0.5-1) and sodium sulfamate in a water-hydrochloric acid mixture to form the reaction product NP-S, combined with the urea-formaldehyde resin adhesive and the modified porphyrin-type cobalt antibacterial agent N-Co, and the antibacterial ultra-thin fiberboard was formed by hot pressing and drying.
It achieves a long-lasting antibacterial effect on ultra-thin fiberboard without affecting the mechanical properties of the fiberboard and avoids secondary pollution.
Smart Images

Figure BDA0004334781070000021 
Figure BDA0004334781070000022 
Figure BDA0004334781070000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of antibacterial wood materials, and in particular relates to an antibacterial ultra-thin fiberboard and a preparation method thereof. Background Art
[0002] As a new type of fiberboard, ultra-thin fiberboard expands and extends the use of high-density ultra-thin fiberboard, replacing most uses of cardboard that is more polluting and has high production costs, and has broad prospects. In particular, ultra-thin fiberboard is currently used as a surface material in decorative panels, and the improvement of antibacterial properties is crucial.
[0003] Antibacterial is a major research direction in the field of household materials. Controlling and eliminating the growth and reproduction of pathogenic microorganisms, producing environmentally friendly antibacterial artificial boards, and creating a healthy and comfortable living environment for humans are important topics in the artificial board industry.
[0004] At present, salicylanilide, carbendazim, antibacterial agent, boric acid, etc. are mostly used as antibacterial agents for antibacterial treatment of artificial boards. Their antibacterial effects are acceptable, but they have a great impact on the bonding strength of the boards and there is secondary pollution. Summary of the invention
[0005] The present invention is developed in view of the above technical problems, and aims to provide an antibacterial ultra-thin fiberboard and a preparation method thereof which can obtain good antibacterial properties without affecting the mechanical properties of the fiberboard.
[0006] Add phosphorus-based oxazolidinone and sodium aminosulfonate in a molar ratio of 1:(0.5-1) into a heatable container containing an appropriate amount of a water-hydrochloric acid mixture, wherein the water-hydrochloric acid mixture is a mixture of water and hydrochloric acid with a mass percentage concentration of 37% in a mass ratio of 10:(1.2-1.5), and react at 60-80°C for 3-6 hours, then continue stirring while naturally cooling to 25-28°C to obtain a reaction solution containing a reaction product NP-S, wherein the molecular formula of NP-S is:
[0007]
[0008] The reaction liquid is added to a urea-formaldehyde resin adhesive having a solid content of 50-60%, wherein the mass ratio of the urea-formaldehyde resin adhesive to the reaction liquid 1 is 1:(0.1-0.5), and after sufficient stirring, a NaOH aqueous solution is added to adjust the pH value to 7.0-7.2 to obtain an antibacterial adhesive 1.
[0009] Add sodium tetraoxalate modified porphyrin type cobalt antibacterial agent N-Co to antibacterial adhesive 1, wherein the mass ratio of antibacterial adhesive 1 to N-Co is 100:(10-15), and mix them evenly to obtain antibacterial adhesive 2, wherein the molecular formula of N-Co is:
[0010]
[0011] 50-100 mesh wood fibers with a moisture content of 3-3.5% and antibacterial adhesive 2 with a weight of 10-15% of the wood fiber are uniformly mixed in a glue mixer, and the mixed wood fibers are dried to obtain a paving material with a moisture content of 6.0-6.5%.
[0012] The paving material is laid into a continuous slab strip, and the target slab thickness is set to 1.2mm and the fiberboard density is 800Kg / m 3 The slab strip is sent to the hot press for hot pressing. The hot press is arranged with two continuous pressure zones according to the forward direction of the slab strip. The hot pressing temperature of zone 1 is 150-170°C, the pressure is 35bar-50bar, and the hot pressing speed is 50m / min. The hot pressing temperature of zone 2 is 130-140°C, the hot pressing speed is 300m / min, and the pressure is 120bar-150bar. The drying process is carried out at a temperature of 50-70°C.
[0013] Furthermore, the method may also include: cooking the qualified wood chips at a cooking pressure of 7.5 bar to 8.0 bar, a cooking temperature of 160° C. to 165° C., and a cooking time of 3.5 min to 4.0 min; adding melted 58# fully refined paraffin wax to the cooked wood chips and hot grinding them to obtain 50-100 mesh wood fibers.
[0014] The preparation method of N-Co is as follows: placing porphyrin-type cobalt and sodium tetraoxalate in a molar ratio of 1:1 in a heatable container, adding an appropriate amount of a water-ethanol mixture and stirring evenly, wherein the mass ratio of water to ethanol is 10:(1-1.5); heating the temperature to 80-110°C at a heating rate of 8-10°C / min and reacting for 12-14h, cooling to room temperature after the reaction is completed, then adding an appropriate amount of water, filtering and drying to obtain N-Co white powder.
[0015] According to the present invention, long-lasting antibacterial properties are achieved by thermal polymerization during the hot pressing process, and by controlling the drying process, the functional groups of the urea-formaldehyde resin are exposed. The urea-formaldehyde resin can be complexed and adsorbed with the Na groups on the antibacterial agent N-Co and NP-S, which is presumed to be a factor in ensuring the mechanical strength of the fiberboard. On the other hand, the adhesive is complexed with the Na group end of the antibacterial agent to ensure that the functional end of the antibacterial agent is free, and the longer chain structure of the free end of NP-S and the repulsion between the amino group on N-Co and the amino group of the adhesive are both conducive to the performance of the free end function. NP-S inhibits bacteria by inhibiting protein synthesis, and cooperates synergistically with the metal antibacterial effect of N-Co. It is presumed that the favorable space of the free end contributes to the synergistic cooperation. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. The described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0017] The ultra-thin high-density fiberboard defined in GB / T18259-2009 and LY / T 1717-2007 is applicable to the present invention: ultra-thin high-density fiberboard is made of wood or other plants as raw materials, prepared by fiber, applied with synthetic resin, and pressed under heating and pressure to a thickness of no more than 1.5 mm and a nominal density of no less than 0.8 g / cm 3 of the board.
[0018] The present invention aims to contribute to the antibacterial function of ultra-thin high-density fiberboard, and proposes the following scheme in detail.
[0019] An appropriate amount of water and hydrochloric acid with a mass percentage concentration of 37% are added to a heatable container for mixing, the mass ratio of water to hydrochloric acid is 1:(1.2-1.5), and then phosphorus-based oxazolidinone and sodium aminosulfonate are added in a molar ratio of 1:(0.5-1), and stirred at 60-80° C. for 3-6 hours, and then stirred and naturally cooled to 25-28° C., preferably stirred at 70-80° C. for 5-6 hours, and then stirred and naturally cooled to 27-28° C. According to this process, a reaction solution containing the reaction product NP-S is obtained.
[0020] In the embodiments, if there is no special statement, the numerical range "A to B" refers to A or more (greater than or equal to A) and B or less (less than or equal to B). When normal temperature or room temperature is mentioned, it usually refers to 22 to 25°C, and sometimes refers to 20 to 28°C depending on different processes. When some processes are limited by temperature, it is generally considered to be carried out at the normal temperature or room temperature.
[0021] The molecular formula of NP-S is:
[0022]
[0023] NP-S is produced by the reaction of phosphorus-based oxazolidinone and sodium aminosulfonate. The molecular formula of phosphorus-based oxazolidinone is as follows:
[0024]
[0025] The reaction equation for the above process is:
[0026]
[0027] The reaction solution is added to a urea-formaldehyde resin adhesive having a solid content of 50-60%, wherein the mass ratio of the urea-formaldehyde resin adhesive to the reaction solution is 1:(0.1-0.5), and the mass ratio is preferably 1:(0.1-0.3). After sufficient stirring, an aqueous NaOH solution is added to adjust the pH value to 7.0-7.2, and the concentration of the aqueous NaOH solution can be, for example, 1-3 mol / L. According to this process, an antibacterial adhesive 1 is obtained.
[0028] Sodium tetraoxalate modified porphyrin-type cobalt antibacterial agent N-Co is added to antibacterial adhesive 1, wherein the mass ratio of antibacterial adhesive 1 to N-Co is 100:(10-15), and the mass ratio is preferably 100:(10-12), and the antibacterial adhesive 2 is obtained by uniformly blending.
[0029] The molecular formula of N-Co is:
[0030]
[0031] N-Co was prepared by the following method:
[0032] Porphyrin-type cobalt and sodium tetraoxalate in a molar ratio of 1:1 are placed in a heatable container, and a proper amount of water-ethanol mixture is added and stirred evenly, wherein the mass ratio of water to ethanol is 10:(1-1.5); the temperature is raised to 80-110°C at a heating rate of 8-10°C / min and the reaction is performed for 12-14h. After the reaction is completed, the mixture is cooled to room temperature, and then a proper amount of water is added. The mixture is filtered and dried to obtain N-Co white powder.
[0033] A specific N-Co preparation example is provided here.
[0034] Preparation Example 1
[0035] 1mmol of porphyrin-type cobalt and 1mmol of sodium tetraoxalate were placed in a 1000mL heatable container, and 500mL of a mixture of water and ethanol was added and stirred evenly, with the mixing ratio of water to ethanol being 10:1. The temperature was raised to 110°C at a rate of 10°C / min, and the reaction was continued for 12h. After the reaction was completed, the mixture was cooled to room temperature, and then 100ml of water was added to the reaction solution, and a white powder was obtained after filtration and drying.
[0036] Preparation Example 2
[0037] 1mmol of porphyrin-type cobalt and 1mmol of sodium tetraoxalate were placed in a 1000mL heatable container, and 500mL of a mixture of water and ethanol was added and stirred evenly, with the mixing ratio of water to ethanol being 10:1.5. The temperature was raised to 80°C at a rate of 8°C / min, and the reaction was carried out for 14h. After the reaction was completed, the mixture was cooled to room temperature, and then 100ml of water was added to the reaction solution, and a white powder was obtained after filtration and drying.
[0038] In the above preparation, N-Co is generated by the reaction of porphyrin-type cobalt and sodium tetraoxalate. The molecular formula of porphyrin-type cobalt is as follows:
[0039]
[0040] The reaction equation for the above reaction is:
[0041]
[0042] 50-100 mesh wood fibers with a moisture content of 3-3.5% and antibacterial adhesive 2 with a weight of 10-15% of the wood fiber are uniformly mixed in a glue mixer, and the mixed wood fibers are dried to obtain a paving material with a moisture content of 6.0-6.5%.
[0043] 50-100 mesh wood fiber can be prepared by washing logs and mechanical cutting, preferably by steaming and hot grinding. Steaming can soften the wood, and use water to swell the non-crystalline area of cellulose, hemicellulose and lignin, providing free volume space for the violent movement of molecules. After the wood is hydrothermally treated, a part of the hemicellulose is easily decomposed and dissolved into a liquid state, and the free hydroxyl groups on the molecular chains of the amorphous area of cellulose absorb water, so that the water film in the cellulose gap thickens, the distance between molecules increases, and the attraction decreases, which is convenient for relative sliding under the action of external forces. As an embodiment, the qualified wood chips are steamed, the steaming pressure is 7.5-8.0 bar, the steaming temperature is 160-165°C, and the steaming time is 3.5-4.0 min. The steamed wood chips are sent to the hot mill, and the melted grinding aid is added thereto. As an embodiment, the grinding aid uses 58# fully refined paraffin wax, and the addition amount is controlled to be 8-10 kg / m 3 . The qualified wood chips are wood chips with a length of 5 to 8 cm, a width of 5 to 8 cm, a thickness of 1 to 2 cm, and a moisture content of 55 to 65%. The preparation of qualified wood chips includes washing and dehydration, and the moisture content of the wood chips is controlled to be 55 to 65%. The preparation of qualified wood chips also includes preheating the washed wood chips, and controlling the preheating temperature to be 90 to 98°C. The preparation of qualified wood chips also includes extruding the preheated wood chips into wooden plugs by a variable diameter spiral. The following provides an example of the preparation of wood fiber.
[0044] Preparation Example 3
[0045] The New Zealand radiata pine logs are flaked with a flaker. The length and width of the wood chips after flaking are in the range of 5 to 8 cm, and the thickness is 1 to 2 cm. The planed wood chips are washed and dehydrated, and then sent to the preheating buffer bin in front of the hot mill through a closed conveyor belt for temporary storage. After being squeezed by a variable diameter spiral, they are formed into wood plugs and sent to the vertical cooker for cooking and softening treatment. The cooking pressure is 7.5 bar, the cooking temperature is 162°C, and the cooking time is 3.5 minutes. The cooked wood chips are sent to the hot mill for hot grinding, and melted 58# fully refined paraffin is added to them, with an addition amount of 8kg / m 3 , 50-100 mesh pine fibers are obtained, and qualified fibers enter the drying pipeline, the pipeline temperature is controlled at 60℃, and the fiber moisture content is 3%.
[0046] Preparation Example 4
[0047] The New Zealand radiata pine logs are flaked with a flaker. The length and width of the wood chips after flaking are 5 to 8 cm, and the thickness is 1 to 2 cm. The planed wood chips are washed and dehydrated, and then sent to the preheating buffer bin in front of the hot mill through a closed conveyor belt for temporary storage. After being squeezed by a variable diameter screw, they are formed into wood plugs and sent to the vertical cooker for cooking and softening treatment. The cooking pressure is 8 bar, the cooking temperature is 164°C, and the cooking time is 4 minutes. The cooked wood chips are sent to the hot mill for hot grinding, and melted 58# fully refined paraffin is added to them, with an addition amount of 10kg / m 3 , 50-100 mesh pine fibers are obtained, and qualified fibers enter the drying pipeline, the pipeline temperature is controlled at 70℃, and the fiber moisture content is 3.5%.
[0048] The wood fiber after mixing with glue is dried to obtain a paving material with a moisture content of 6.0-6.5%. The drying process is preferably carried out at a temperature of 50-70°C. The paving material is paved into a continuous slab strip, and the target board thickness is set to 1.2mm and the fiberboard density is 800Kg / m 3 The slab strip is sent to the hot press for hot pressing. The hot press is arranged with two continuous pressure zones according to the forward direction of the slab strip. The hot pressing temperature of zone 1 is 150-170℃, the pressure is 35bar-50bar, and the hot pressing speed is 50m / min. The hot pressing temperature of zone 2 is 130-140℃, the hot pressing speed is 300m / min, and the pressure is 120bar-150bar.
[0049] The following specifically provides examples and comparative examples of the preparation of antibacterial ultra-thin fiberboards.
[0050] Example 1
[0051] 150g of 37% concentrated hydrochloric acid was added to a reaction kettle containing 1000mL of water, and then 1mmol of phosphorus-based oxazolidinone and 0.5mmol of sodium aminosulfonate were added, and the mixture was stirred at 75°C for 3h, and then naturally cooled to 25°C during stirring to obtain NP-S reaction solution. 10g of NP-S reaction solution was added to 100g of urea-formaldehyde resin adhesive with a solid content of 50%, and after sufficient stirring, an aqueous NaOH solution was added to adjust the pH to 7.0 to prepare antibacterial adhesive 1. 100g of antibacterial adhesive 1 was weighed again, and 10g of sodium tetraoxalate modified porphyrin type cobalt antibacterial agent N-Co was added, and the mixture was fully mixed to obtain antibacterial adhesive 2. 50-100 mesh wood fiber with a moisture content of 3% and antibacterial adhesive 2 with a wood fiber mass of 10% were mixed evenly in a glue mixer, and the mixed wood fiber was dried to obtain a paving material with a moisture content of 6.0%. The paving material is laid into a continuous slab strip, and the target slab thickness is set to 1.2mm and the fiberboard density is 800Kg / m 3 The slab strip is sent to the hot press for hot pressing. The hot press is arranged with two continuous pressure zones according to the forward direction of the slab strip. The hot pressing temperature in zone 1 is 150℃, the pressure is 50bar, and the hot pressing speed is 50m / min. The hot pressing temperature in zone 2 is 130℃, the hot pressing speed is 300m / min, and the pressure is 120bar. The hot pressed sheet is transferred to the plate turning rack through the conveyor belt for cooling and subsequent stacking and packaging.
[0052] Example 2
[0053] 120g of 37% concentrated hydrochloric acid was added to a reactor containing 1000mL of water, and then 1mmol of phosphorus-based oxazolidinone and 1mmol of sodium aminosulfonate were added, and the mixture was stirred at 65°C for 3h, and then naturally cooled to 28°C during stirring to obtain NP-S reaction solution. 50g of NP-S reaction solution was added to 100g of urea-formaldehyde resin adhesive with a solid content of 60%, and after sufficient stirring, an aqueous NaOH solution was added to adjust the pH to 7.2 to prepare antibacterial adhesive 1. 15g of sodium tetraoxalate modified porphyrin-type cobalt antibacterial agent N-Co was added to 100g of antibacterial adhesive 1, and the mixture was fully mixed to obtain antibacterial adhesive 2. 50-100 mesh wood fiber with a moisture content of 3.5% and antibacterial adhesive 2 with a wood fiber mass of 10% were mixed evenly in a glue mixer, and the mixed wood fiber was dried to obtain a paving material with a moisture content of 6.5%. The paving material is laid into a continuous slab strip, and the target slab thickness is set to 1.2mm and the fiberboard density is 800Kg / m 3The slab strip is sent to the hot press for hot pressing. The hot press is arranged with two continuous pressure zones according to the forward direction of the slab strip. The hot pressing temperature in zone 1 is 170℃, the pressure is 35bar, and the hot pressing speed is 50m / min. The hot pressing temperature in zone 2 is 140℃, the hot pressing speed is 300m / min, and the pressure is 150bar. The hot pressed sheet is transferred to the plate turning rack through the conveyor belt for cooling and subsequent stacking and packaging.
[0054] Example 3
[0055] 135g of 37% concentrated hydrochloric acid was added to a reactor containing 1000mL of water, and then 1mmol of phosphorus-based oxazolidinone and 0.5mmol of sodium sulfamate were added, and the mixture was stirred at 80°C for 6h, and then naturally cooled to 25°C during stirring to obtain NP-S reaction solution. 30g of NP-S reaction solution was added to 100g of urea-formaldehyde resin adhesive with a solid content of 50%, and after sufficient stirring, an aqueous NaOH solution was added to adjust the pH to 7.0 to prepare antibacterial adhesive 1. 12g of sodium tetraoxalate modified porphyrin-type cobalt antibacterial agent N-Co was added to 100g of antibacterial adhesive 1, and the mixture was fully mixed to obtain antibacterial adhesive 2. 50-100 mesh wood fiber with a moisture content of 3.5% and antibacterial adhesive 2 with a weight of 10% of the wood fiber were mixed evenly in a glue mixer, and the mixed wood fiber was dried to obtain a paving material with a moisture content of 6.5%. The paving material is laid into a continuous slab strip, and the target slab thickness is set to 1.2mm and the fiberboard density is 800Kg / m 3 The slab strip is sent to the hot press for hot pressing. The hot press is arranged with two continuous pressure zones according to the forward direction of the slab strip. The hot pressing temperature in zone 1 is 150℃, the pressure is 40bar, and the hot pressing speed is 50m / min. The hot pressing temperature in zone 2 is 140℃, the hot pressing speed is 300m / min, and the pressure is 120bar. The hot pressed sheet is transferred to the plate turning rack through the conveyor belt for cooling and subsequent stacking and packaging.
[0056] Comparative Example 1
[0057] Comparative Example 1 is designed as a control example 3, except that the wood fibers after mixing with the glue are not dried. The moisture content of the wood fibers after mixing with the glue is measured to be 12%.
[0058] Comparative Example 2
[0059] Comparative Example 1 is designed to control Example 1, except that 50 g of reaction solution 1 is added to 100 g of urea-formaldehyde resin adhesive; N-Co is not added to antibacterial adhesive 1, and the wood fiber is directly glued.
[0060] Tests and Results
[0061] The fiberboard obtained by the embodiment and the comparative example was subjected to antibacterial test and mechanical property test, wherein the antibacterial test was carried out according to LY / T1926-2020, and the results are shown in Table 1 below.
[0062] Table 1:
[0063]
[0064] According to the test results, in Comparative Example 1 in which the moisture content was not controlled after sizing, the antibacterial property and mechanical properties were reduced. Reducing the moisture content to a certain extent is beneficial to the exposure of the functional groups of the urea-formaldehyde resin. The urea-formaldehyde resin can be complexed and adsorbed with the Na group on the antibacterial agent N-Co and NP-S. It is speculated that this is a factor that does not affect the mechanical strength of the fiberboard. On the other hand, the adhesive is complexed with the Na group end of the antibacterial agent to ensure the freedom of the functional end of the antibacterial agent, and the longer chain structure of the free end of NP-S and the repulsion between the amino group on N-Co and the amino group of the adhesive are both beneficial to the performance of the free end function. NP-S inhibits bacteria by inhibiting protein synthesis, and cooperates synergistically with the metal antibacterial effect of N-Co. According to the test, in Comparative Example 2 in which only one antibacterial agent was added, the antibacterial property decreased significantly. It is speculated that the favorable space at the free end promotes synergistic cooperation.
Claims
1. A method for preparing an antibacterial ultra-thin fiberboard, characterized in that: include: Add phosphorus-based oxazolidinone and sodium aminosulfonate in a molar ratio of 1: (0.5-1) into a heatable container containing an appropriate amount of water-hydrochloric acid mixture, stir and react at 60-80° C. for 3-6 hours, then continue stirring and naturally cool to 25-28° C. to obtain a reaction solution containing a reaction product NP-S, wherein the molecular formula of NP-S is: Adding the reaction liquid to a urea-formaldehyde resin adhesive having a solid content of 50-60%, wherein the mass ratio of the urea-formaldehyde resin adhesive to the reaction liquid is 1:(0.1-0.5), stirring thoroughly, adding a NaOH aqueous solution to adjust the pH value to 7.0-7.2, and obtaining an antibacterial adhesive 1; Add sodium tetraoxalate modified porphyrin type cobalt antibacterial agent N-Co to antibacterial adhesive 1, wherein the mass ratio of antibacterial adhesive 1 to N-Co is 100:(10-15), and mix them evenly to obtain antibacterial adhesive 2, wherein the molecular formula of N-Co is: 50-100 mesh wood fibers with a moisture content of 3-3.5% and antibacterial adhesive 2 with a weight of 10-15% of the weight of the wood fibers are mixed evenly in a glue mixer, and the mixed wood fibers are dried to obtain a paving material with a moisture content of 6.0-6.5%; The paving material is laid into a continuous slab strip, and the target slab thickness is set to 1.2mm and the fiberboard density is 800Kg / m 3 The slab strip is sent to the hot press for hot pressing. The hot press is arranged with two continuous pressure zones according to the forward direction of the slab strip. The hot pressing temperature of zone 1 is 150-170℃, the pressure is 35bar-50bar, and the hot pressing speed is 50m / min. The hot pressing temperature of zone 2 is 130-140℃, the hot pressing speed is 300m / min, and the pressure is 120bar-150bar.
2. The preparation method according to claim 1, wherein The water-hydrochloric acid mixed solution is prepared by mixing water with a mass ratio of 10:(1.2-1.5) and hydrochloric acid with a mass percentage concentration of 37%.
3. The preparation method according to claim 1, wherein The drying process is carried out at a temperature of 50 to 70°C.
4. The preparation method according to claim 1, further comprising: The qualified wood chips are steamed at a pressure of 7.5 bar to 8.0 bar, a temperature of 160° C. to 165° C., and a time of 3.5 min to 4.0 min; melted 58# fully refined paraffin is added to the steamed wood chips and hot-grinded to obtain 50-100 mesh wood fibers.
5. The preparation method according to claim 1, wherein N-Co was prepared by the following method: Porphyrin-type cobalt and sodium tetraoxalate in a molar ratio of 1:1 are placed in a heatable container, and an appropriate amount of water-ethanol mixture is added and stirred evenly, wherein the mass ratio of water to ethanol is 10:(1-1.5); the temperature is raised to 80-110°C at a heating rate of 8-10°C / min and the reaction is performed for 12-14h. After the reaction is completed, the mixture is cooled to room temperature, and then an appropriate amount of water is added. The mixture is filtered and dried to obtain N-Co white powder.
6. An antibacterial ultra-thin fiberboard, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Production method of environment-friendly mildew-proof medium density fiberboard
CN105643760A
Crop straw corrosion-resistant antibacterial flame-retardant fiberboard and preparation method thereof
CN108608550A